Splitting analysis of the second-generation rice hybrid ‘Bakhus x Kontakt’ - P. I. Kostylev; E. V. Krasnova (Зерновое хозяйство России)
The current paper has presented the study results of the second-generation hybrid population of ‘Bakhus x Kontakt’ combination. The variety ‘Bakhus’ is large-kernelled, vigorously growing, tall, unresistant to lodging, the variety ‘Kontakt is short, resistant to lodging, medium-kernelled. The purpose of the study was to analyze the inheritance of a number of quantitative traits in the F2 rice hybrid ‘Bakhus x Kontakt’ and select the best plants for the further breeding process. In the process of hybridological analysis, there have been established the patterns of inheritance of the main quantitative traits affecting productivity, there have been identified the best undersized forms, in which there were formed compact erect panicles and large kernels, and there has been selected the source material for breeding work. The study was carried out on the plots of OP «Proletarskoe» in the Rostov region in 2019–2021. The crossing was carried out in 2019, F1 was reproduced in 2020, F2 rice plants were grown in 2021. There has been found that according to ‘plant height’ there was a partial dominance of lower trait values and allelic differences in parental varieties for one pair of genes. There was no dominance according to ‘panicle length’; there were found digenic differences in the initial varieties. According to the trait ‘number of spikelets in a panicle’, there was a dominance of large values and positive transgression. According to spikelet length in F2 hybrids, there was a wide variation of the trait within the variability of parental varieties from 6.8 to 11.0 mm. there was no dominance. There was noted a digenic splitting in a ratio of 1:4:6:4:1. According to 1000-kernel weight, there has been identified a monohybrid splitting of 3:1. There were selected the best morphotype F2 forms, which differed in optimal plant height, long panicles, their increased kernel percentage and 1000-kernel weight.